Principal Service Strategy in Improving the Quality of Junior High School Education in Favorite Schools in Sabang City - Intan, Cut; Novita, Rita; Khausar, Khausar (FKIP - Universitas Riau, 2025)
This study aims to describe and analyze the planning, implementation, monitoring, evaluation and supporting factors and obstacles of the Principal's service strategy in improving the quality of education in Favorite Schools in Sabang City. The research subjects include three schools, namely State Junior High School 1 Sabang, State Islamic High School 1 Sabang and Pondok Pesantren Sulaimaniyah Sabang City. This research method is descriptive with a qualitative type using data collection techniques through interviews, observation and documentation. Research informants consist of the Principal, School Supervisor, Deputy Head of Curriculum, Deputy Head of Student Affairs, Deputy Head of Facilities and Infrastructure, Homeroom Teachers, Guidance and Counseling Teachers, Subject Teachers, Parents/School Kumite and Students. The results of the study indicate that the results of the study indicate that the principal's strategy can improve the quality of education in the three Favorite schools in Sabang City.